ANALISIS FAKTOR-FAKTOR PENYEBAB KREDIT MACET PADA PT. PEGADAIAN PERSERO SUMBAWA BESAR - Abdul Rahim; R Rostriningsi (Jurnal Ekonomi & Bisnis, 2023)
This study aims to examine the influence of the factors that cause bad credit at PT. Pegadaian Persero Sumbawa Besar consisting of education, employment and income. This research uses associative method. The type of data used is quantitative data in the form of the results of research respondents' answers which are scored (scoring) which are obtained directly through distributing questionnaires. The respondents of this research are all customers of PT. Pegadaian Persero Sumbawa Besar totaling 30 people. All data that has been collected will be processed using the SPSS program to be studied using techniques which include multiple linear regression analysis, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that partially education and employment have no effect on bad loans at PT. Pegadaian Persero Sumbawa Besar, while income partially has a negative and significant effect on bad loans at PT. Pawnshop Persero Sumbawa Besar. Simultaneously education, employment and income have a significant effect on bad loans at PT. Pawnshop Persero Sumbawa Besar. The ability of the variables of education, employment and income to variations in bad credit variables at PT. Pegadaian Persero Sumbawa Besar is 25.3%, while the remaining 74.7% is influenced by other variables not examined, such as character, interest rates, economic conditions, and others.